2012
DOI: 10.1002/lary.23673
|View full text |Cite
|
Sign up to set email alerts
|

Current use of intralesional cidofovir for recurrent respiratory papillomatosis

Abstract: Eighteen statements were approved by the RRP Task Force after discussion of the survey results. Intralesional cidofovir may be initiated if surgical debulking is required every 2 to 3 months. The concept of an adjuvant regimen with regular biopsy is favored. Administration should remain below established safe limits of dosing (3 mg/kg) and volume. Informed consent, including discussion of off-label use and acute kidney injury in children, is important. A special consent form sample is included. There remains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 15 publications
0
33
1
2
Order By: Relevance
“…CDV has also been employed to manage recalcitrant cases of verruca vulgaris, mosaic verruca plana, and different skin lesions caused by HPV (Stragier et al, 2002;Bonatti et al, 2007;Kralund et al, 2011;Field et al, 2009). Importantly, following the first report on the use of CDV for the treatment of severe RRP in 1998 (Snoeck et al, 1998), the application of the drug as adjuvant therapy for severe cases of RRR has been documented by several investigators (Derkay et al, 2013;Mikolajczak et al, 2012;Ksiazek et al, 2011;Derkay and Wiatrak, 2008). Although there were some anecdotal reports documenting serious adverse reactions in RRP in off-label use of CDV (Tjon Pian Gi et al, 2012), a multicentre retrospective chart review involving 16 hospitals from 11 countries worldwide with 635 RRP patients (of whom 275 were treated with CDV) was performed.…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 94%
See 1 more Smart Citation
“…CDV has also been employed to manage recalcitrant cases of verruca vulgaris, mosaic verruca plana, and different skin lesions caused by HPV (Stragier et al, 2002;Bonatti et al, 2007;Kralund et al, 2011;Field et al, 2009). Importantly, following the first report on the use of CDV for the treatment of severe RRP in 1998 (Snoeck et al, 1998), the application of the drug as adjuvant therapy for severe cases of RRR has been documented by several investigators (Derkay et al, 2013;Mikolajczak et al, 2012;Ksiazek et al, 2011;Derkay and Wiatrak, 2008). Although there were some anecdotal reports documenting serious adverse reactions in RRP in off-label use of CDV (Tjon Pian Gi et al, 2012), a multicentre retrospective chart review involving 16 hospitals from 11 countries worldwide with 635 RRP patients (of whom 275 were treated with CDV) was performed.…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 94%
“…In another recent study, it was concluded that CDV remains the leading option for adjuvant treatment of patients with RRP of all ages whose disease is difficult to manage with surgery alone. CDV represents an option to reduce the risks of frequent surgical debulking and airway obstruction in children and adults with recurrent or severe disease (Derkay et al, 2013). CDV is nowadays recognized as an adjuvant therapy for the management of this disease (Tjon Pian Gi et al, 2013;Graupp et al, 2013).…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 99%
“…The role of cidofovir in the therapy of recurrent laryngeal papillomatosis has not yet been sufficiently evaluated. Several studies have shown that when locally applied, cidofovir is virustatic without any side effects and, in particular, is able to significantly reduce the rate of recurrence [12,13]. The importance of evaluating the impact of any disease on the patient's quality of life and the outcome of various therapeutic interventions is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…La Recurrent Respiratory Papillomatosis Task Force recomienda la utilización de cidofovir intralesional en pacientes que requieren procedimientos quirúrgicos laríngeos cada 2 o 3 meses. 9 Se han probado interferon alpha, antivirales (acyclovir, cidofovir, ribavirin), vacuna contra el HPV, terapia génica. No se ha observado curación con estos tratamientos.…”
Section: Discussionunclassified